Reshaping Location Decisions in Uncertainty: Sectoral FDI Trends in Indonesia - Nofiani, Delly; Nur Arumsari, Devinta (Lembaga Penelitian Universitas YARSI, 2025)
This study examines changes in foreign direct investment (FDI) location and sectoral patterns in Indonesia before and during the COVID-19 pandemic by comparing primary, secondary, and tertiary sectors using descriptive quantitative analysis of BKPM data from 2019–2022. The findings reveal persistent sectoral and geographical differences: primary sector FDI remains concentrated in resource-rich regions such as Sumatra and Kalimantan, while secondary and tertiary sector investments continue to cluster in Java, particularly in industrial and urban areas. Despite the global uncertainty caused by the pandemic, no fundamental shift in sectoral location preferences is observed, indicating structural stability in Indonesia’s FDI determinants. The study contributes original insights by integrating sectoral classification with sub-national location analysis during a crisis period, an aspect that has received limited attention in prior FDI literature. The implications of this research are twofold: theoretically, it extends FDI location theory by demonstrating the resilience of sector-specific location advantages under conditions of uncertainty; practically, it provides policymakers with evidence to design targeted regional investment strategies that align infrastructure development, resource endowments, and market accessibility with sectoral investment needs in emerging markets such as Indonesia